Prokinetics for functional dyspepsia - Pittayanon, Rapat (Cochrane Database Syst Rev, 2018)
BACKGROUND: Dyspepsia is a common condition associated with gastrointestinal (GI) disease. Prokinetics are the treatment of choice for functional dyspepsia (FD). However, the role of prokinetics in FD treatment is still controversial. OBJECTIVES: We conducted a systematic review and meta‐analysis of randomised control trials (RCTs) examining the efficacy of prokinetics in the treatment of FD. The primary outcome was overall absence of or improvement of symptoms and symptom scores at the end of treatment. We also evaluated quality of life (QoL) and adverse events as secondary outcomes. SEARCH METHODS: We performed a systematic search of MEDLINE, Embase, the Cochrane Library, and CINAHL, from 1946 until September 2017. RevMan 5.3 was used to calculate pooled risk ratios (RR) of symptoms persisting or without improved QoL or adverse events, mean difference (MD) or standardised mean difference (SMD) of post‐treatment symptoms scores, changes of symptom scores, and QoL, when appropriate with 95% confidence intervals (CI), using a random‐effects model. Quality of evidence was evaluated using GRADE methodology. SELECTION CRITERIA: We included studies that were parallel group RCTs comparing one prokinetic with either placebo or another prokinetic of the same or different class for the treatment of FD. Studies involved adults who presented with dyspepsia symptoms and who had negative or insignificant findings on endoscopy as well as no other organic and metabolic disorders. Studies only including participants with primarily reflux or heartburn symptoms were excluded. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed study eligibility, study quality and performed data extraction. MAIN RESULTS: From an initial 1388 citations, we identified 43 studies in 40 papers. Of those, 29 studies with 10,044 participants compared six prokinetics with placebo for the outcome of absence of symptoms or symptom improvement. There was a statistically significant effect of prokinetic treatment in reducing global symptoms of FD (RR of remaining dyspeptic = 0.81, 95% CI 0.74 to 0.89; number needed to treat for an additional beneficial outcome (NNTB) =7, very low‐quality evidence) with considerable heterogeneity; I(2) = 91% (P < 0.00001). After removing cisapride from the analysis, the effect of prokinetics in global symptom improvement still persisted, compared to placebo (RR 0.87, 95% CI 0.80 to 0.94), but was still based on very low‐quality evidence. The result showed persistence of significant improvement in subgroups of studies at unclear or at low risk of bias (RR 0.86, 95% CI 0.80‐0.92), and in subgroups by molecules of cisapride (RR 0.71, 95% CI 0.54 to 0.93; NNTB = 4), acotiamide (RR 0.94, 95% CI 0.91 to 0.98; NNTB = 20) and tegaserod(RR 0.89, 95% CI 0.82 to 0.96; NNTB = 14). Ten studies compared different types of prokinetics with each other and the most commonly used comparator was domperidone, 10 mg three times a day (eight of the 10 studies). There was a significantly better post‐treatment symptom score in other prokinetics, compared to domperidone (SMD ‐0.19, 95% CI ‐0.35 to ‐0.03, very low‐quality evidence), but no difference in reducing global symptom (RR 0.94, 95% CI 0.83 to 1.07), and mean difference symptom scores (SMD ‐0.13, 95% CI ‐0.31 to 0.05). We found five studies that assessed quality of life, but there was no benefit in improving quality of life with prokinetic treatment (SMD 0.11, 95% CI ‐0.10 to 0.33; participants = 1774). The adverse events in individual prokinetics was not different from placebo (RR 1.09, 95% CI 0.95 to 1.25; participants = 3811; studies = 17). However, when we looked at the adverse effects by each prokinetic, there were overall greater adverse effects in the active treatment group with cisapride (RR 1.31, 95% CI 1.03 to 1.65; P = 0.03). The most common side effects were diarrhoea, abdominal discomfort and nausea. The funnel plot was asymmetric (Egger's test, P = 0.02) implying reporting bias or other small‐study effects may be, in part, driving the benefit of prokinetics compared to placebo in this meta‐analysis. The GRADE assessment of the quality of the evidence in each outcome are mostly low or very low due to concerns around risk of bias in study design, unexplained heterogeneity and possible publication bias. AUTHORS' CONCLUSIONS: Due to low, or very low, quality of evidence, we are unable to say whether prokinetics are effective for the treatment of functional dyspepsia . We are uncertain which of the individual prokinetic drugs is the most effective as well as whether prokinetics can improve quality of life. Apart from cisapride, prokinetics are well‐tolerated. Good quality RCTs are needed to verify the efficacy of prokinetics.